Immigrant subjectivities in Asian American and Asian diaspora literatures - Ma, Sheng-mei (State University of New York Press, 1998)
This book opens with an interrogation of the representation of immigrants in Asian American and, to a lesser extent, Asian Diaspora literatures, including works by such writers as Maxine Hong Kingston, Frank Chin, Amy Tan, and Bharati Mukherjee. Immigrant subjectivities in these texts are frequently subsumed in the urgent need to self-fashion an Asian American identity, and take the peculiar form of "immigrant schizophrenic." Ma also explores how the drive to "claim America" manifests itself as an eroticization of white bodies in male immigrant and minority writers. He then directs his attention to immigrant self-representation from the unique yet representative positionality of Taiwanese immigrants, as found in overseas student literature and in the recent films of Ang Lee. With a contrapuntal reading of the portrayal of immigrants in Asian American and Asian Diaspora literatures, this book maps out a terrain largely uncharted by scholars of various disciplines